Reducing Admission for Anaphylaxis in a Pediatric Emergency Department Using a Clinical Decision Support Tool. Issue 5 (8th September 2022) - Wolpert, Katherine H.; Kestle, Rebecca; Weaver, Nicholas; Huynh, Kelly; Yoo, Minkyoung; Nelson, Richard; Lane, Roni D.
Abstract : Introduction: Anaphylaxis is a life-threatening condition necessitating emergent management. However, the benefits of prolonged observation and indications for hospitalization are not well established. Through the implementation of a disposition-focused clinical decision support tool (CDST), this quality improvement initiative aimed to reduce hospitalization for low-risk patients presenting to the pediatric emergency department (PED) with anaphylaxis from 49% to ≤12% within 12 months of implementation. Methods: The intervention included patients 18 years and younger of age presenting with anaphylaxis to the PED. A multidisciplinary team identified a 2006 evidence-based guideline as a significant contributor to hospitalization. The updated guideline incorporated a disposition-focused CDST that stratified patients as low-risk or high-risk and recommended discharge of low-risk patients after a 4-hour observation period. The primary outcome measure was the percentage of low-risk patients hospitalized. Balancing measures included low-risk patient 72-hour return rate and PED length of stay for all comers. Secondary outcomes included a focused cost analysis. Results: Fifty-three children preintervention and 43 children postintervention presenting with anaphylaxis met low-risk criteria. Postimplementation, hospitalization of low-risk patients decreased from 49% to 7% ( P < 0.0001). No low-risk patients returned in 72 hours for an anaphylaxis-related concern ( P = 0.83). The median PED length of stay increased from 189 to 193 minutes ( P < 0.0001). The median cost per low-risk encounter decreased by 377 ( P = 0.013). Conclusions: After implementing an evidence-based disposition-focused CDST, hospitalization of low-risk patients presenting to the PED with anaphylaxis significantly decreased without an increase in 72-hour returns. In addition, patient encounters demonstrated cost savings.